2010
DOI: 10.1002/dta.158
|View full text |Cite
|
Sign up to set email alerts
|

Screening for the synthetic cannabinoid JWH‐018 and its major metabolites in human doping controls

Abstract: Referred to as 'spice', several new drugs, advertised as herbal blends, have appeared on the market in the last few years, in which the synthetic cannabinoids JWH-018 and a C(8) homologue of CP 47,497 were identified as major active ingredients. Due to their reported cannabis-like effects, many European countries have banned these substances. The World Anti-Doping Agency has also explicitly prohibited synthetic cannabinoids in elite sport in-competition. Since urine specimens have been the preferred doping con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 19 publications
3
73
0
2
Order By: Relevance
“…Analysis of human urine from individuals known to have ingested either JWH-018 or JWH-073 have identified several products of Phase I and II metabolism (Moller et al, 2010;Sobolevsky et al, 2010;Beuck et al, 2011;Grigoryev et al, 2011;Moran et al, 2011;Schneir et al, 2011). Many of these hydroxylated metabolites have been shown to be monohydroxy derivatives of the naphthalene, indole, or side-chain moieties (Sobolevsky et al, 2010) that are excreted in urine primarily as glucuronic acid conjugates (Sobolevsky et al, 2010;Wintermeyer et al, 2010;Moran et al, 2011), thus implicating the involvement of UGTs in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of human urine from individuals known to have ingested either JWH-018 or JWH-073 have identified several products of Phase I and II metabolism (Moller et al, 2010;Sobolevsky et al, 2010;Beuck et al, 2011;Grigoryev et al, 2011;Moran et al, 2011;Schneir et al, 2011). Many of these hydroxylated metabolites have been shown to be monohydroxy derivatives of the naphthalene, indole, or side-chain moieties (Sobolevsky et al, 2010) that are excreted in urine primarily as glucuronic acid conjugates (Sobolevsky et al, 2010;Wintermeyer et al, 2010;Moran et al, 2011), thus implicating the involvement of UGTs in this process.…”
Section: Discussionmentioning
confidence: 99%
“…These products are typically vegetative material laced with these potent CB-receptor agonists, and recent clinical data provide evidence of development of anxiety (Schneir et al, 2011), tolerance (Zimmermann et al, 2009), and enhancement of psychoses (Every-Palmer, 2010) in individuals using these products. There is also an evolving body of information available on the metabolism of synthetic cannabinoids, JWH-018 and JWH-073, in body fluids (Moller et al, 2010;Sobolevsky et al, 2010;Beuck et al, 2011;Grigoryev et al, 2011;Moran et al, 2011) and in vitro . Continued characterization of these metabolic pathways is important because recent studies have shown that oxidized products of JWH-018 retain significant in vitro and in vivo activity (L. K. Brents, E. E. Reichard, S. M. Zimmerman, J. H. Moran, W. E. Fantegrossi, and P. L. Prather, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Most synthetic cannabinoids are eliminated via CYP metabolism, with further glucuronidation by UDPGT (phase II enzymes). Oxidative metabolites and glucuronide conjugates predominate with negligible parent compound present in human urine (16)(17)(18). Thus, it is essential to characterize metabolic profiles of synthetic cannabinoids to identify target analytes that effectively document their consumption during clinical and forensic urine testing.…”
Section: Introductionmentioning
confidence: 99%
“…Tarım ilaçları, floresan tozu, yavşan otu, sanayi kimyasalları gibi birçok madde sentetik kannabinoid ile karıştırılabildiği medyaya yansımıştır. Kan ve idrar düzey-leri tespit edilemediği için, hangi olguda hangi etkiyi yaptı-ğının bilinmemesi de tanı ve tedavide yaşanacak bir başka ciddi olumsuzluktur (6,8,9). Yapılan bir çalışmada lipofilik kimyasal yapılarından ötürü intravenöz lipit tedavisinin etkili olduğu belirtilse de (10), yukarda aktarmaya çalıştığımız semptomatik tedaviler haricinde bilinen spesifik bir antidot veya tedavisi yoktur.…”
unclassified